2019
DOI: 10.3390/ijerph16193756
|View full text |Cite
|
Sign up to set email alerts
|

Co-producing Progression Criteria for Feasibility Studies: A Partnership between Patient Contributors, Clinicians and Researchers

Abstract: There is a lack of guidance for developing progression criteria (PC) within feasibility studies. We describe a process for co-producing PC for an ongoing feasibility study. Patient contributors, clinicians and researchers participated in discussions facilitated using the modified Nominal Group Technique (NGT). Stage one involved individual discussion groups used to develop and rank PC for aspects of the trial key to feasibility. A second stage involving representatives from each of the individual groups then d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
(87 reference statements)
1
18
0
Order By: Relevance
“…For recruitment and retention, 50% and 75% were selected, respectively, as we recognised that not all patients may want to participate in research while in hospital and that the intervention (being technology-based) may not appeal to some patients. The values selected are consistent with those developed for a similar randomised controlled feasibility study of a complex intervention to reduce frailty and falls among haemodialysis patients [27].…”
Section: Study Overview and Aimssupporting
confidence: 71%
“…For recruitment and retention, 50% and 75% were selected, respectively, as we recognised that not all patients may want to participate in research while in hospital and that the intervention (being technology-based) may not appeal to some patients. The values selected are consistent with those developed for a similar randomised controlled feasibility study of a complex intervention to reduce frailty and falls among haemodialysis patients [27].…”
Section: Study Overview and Aimssupporting
confidence: 71%
“…For each criterion, the development of ‘stop’ (indicating when there are issues with the trial that cannot be resolved) and ‘go’ thresholds (when there are no issues that may impede the success of a trial) were co-produced by patients, clinicians and researchers. 19 20 Results falling between these thresholds indicated that adaptation to trial procedures may render a definitive RCT viable. 20 …”
Section: Methodsmentioning
confidence: 99%
“…Using this system, green “Go” indicated that all criteria has been met and a future, larger scale randomized trial should proceed, yellow “Amend” indicated that some changes should be made to the larger trial, and red “Stop” indicated that the investigators should not move forward with a larger trial. For our enrollment feasibility, an enrollment of ≥ 50% of qualifying patients was selected [ 19 ]. Progression criteria for cycling feasibility on eligible cycling days of ≥ 70% were chosen [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…For our enrollment feasibility, an enrollment of ≥ 50% of qualifying patients was selected [ 19 ]. Progression criteria for cycling feasibility on eligible cycling days of ≥ 70% were chosen [ 19 ].…”
Section: Methodsmentioning
confidence: 99%